Factors Affecting Organizational Citizenship Behavior - Niamila, Ocvi; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2022)
This study aims to determine the effect of job satisfaction and perceived organizational support on OCB through organizational commitment as a mediating variable on employess of Perumda Air Minum Tirta Mulia Kabupaten Pemalang. The type of research used is quantitative research, with a sample of 97 respondents. Sampling technique using saturated sample. The research analysis method used is intrument test (validity and reability), descriptive analysis test, regression test and path analysis test using SPSS version 23 program. Data collection methods use interview, observation and questionnaire technique. The result showed that job satisfaction and perceived organizational support have a positive and significant effect on organizational commitment. Job satisfaction and organizational commitmen have a positive and significant effect on OCB, but perceived organizational support have a positive and insignificant effect on OCB. Organizational commitment is positive and significant able to be a mediating variable on the relationship between job satisfaction and perceived organizatioanl support on OCB. Suggestions from this research are that the company should be able to improve its employee skills training program, provide oppurtunities for employees to improve their careers, provide rewards for employee achievements and increase gahthering programs with team work in the event.